Effect the Use of Coconut Water Kefir Supplementation on Performance, Carcass, and Gastrointestinal Tract of Broiler Chicken - Deka Uli Fahrodi; Marsudi Marsudi; Nur Saidah Said; Taufik Dunialam Khaliq (Jurnal Agripet)
This study aimed to assess the effects of coconut water kefir (CWK) supplementation on the production performance, carcass characteristics, and gastrointestinal tract morphology of broiler chickens. A total of 400 broiler chickens were used and divided into four treatment groups with five replicates, each containing 20 chickens. The study followed a completely randomized design (CRD). The treatment groups were as follows: T0 (control, no CWK supplementation), T1 (5% CWK), T2 (10% CWK), and T3 (15% CWK). The results indicated that CWK supplementation significantly influenced production performance, including feed intake, final body weight, weight gain, feed conversion ratio, and feed efficiency ratio. Furthermore, CWK supplementation also had a significant effect on carcass traits, such as carcass weight, breast percentage, thigh percentage, and abdominal fat, as well as on gastrointestinal tract parameters, including jejunum percentage, jejunum length, and ileum length. The optimal results were obtained from the 10% CWK supplementation (T2). In conclusion, CWK supplementation effectively improved the production performance, carcass yield, and gastrointestinal tract development in broiler chickens.